Implementación de medidas legales en el Código Orgánico Integral Penal con el fin de evitar el riesgo de ser víctima en lo concerniente al delito de captación ilegal de dinero - Abad Vega, María Fernanda (2023)
The present curricular integration work is titled "Implementation of legal measures in the Comprehensive Criminal Code in order to prevent the risk of becoming a victim of the crime of illegal money laundering." It arises from the multitude of cases reported by individuals who have fallen victim to illegal money laundering operations. These cases typically only reach a preliminary investigation by the Public Prosecutor's Office; however, few of them result in a conviction. In Ecuador, illegal money laundering is considered a crime. Despite being defined as such since August 2014, when the Comprehensive Criminal Code came into effect, there are still shortcomings within this criminal offense. These loopholes have been exploited in recent years by the perpetrators of pyramid scams, who utilize technology to target more victims and dramatically increase their profits. Therefore, in this research, the aim is to offer an alternative solution to address this particular crime. The lack of sufficient doctrinal treatment regarding pyramid schemes and frauds has led to a situation where the perpetrators and their accomplices are not adequately punished in accordance with the prescribed legal measures. As a result, the crime often goes unpunished, leaving the victims without the proper comprehensive restitution they deserve. Based on the information presented earlier, it was employed specific materials and methods to conduct this research. In addition, it was conducted surveys and interviews with legal professionals. The findings from these surveys and interviews were instrumental in formulating a proposed reform to Article 323 of the Comprehensive Criminal Code. The purpose of this proposal is to address the existing legal loopholes within this particular criminal offense and offer a solution.